Cross-cultural adaptation and initial validation of the Brazilian-Portuguese version of the pediatric automated neuropsychological assessment metrics - de Amorim, Jaqueline Cristina (2022)
Automated neuropsychiatric batteries have been used in research and clinical practice, including for chronic diseases, such as Systemic Lupus Erythematosus. The Pediatric Automated Neuropsychological Assessment Metrics battery (Ped-ANAM), originally developed for use in American-English speaking individuals, allows tracking of cognitive functions. It can be applied to people over 9 years old. The aim of this study was to translate and present initial validation data from the Ped-ANAM into Brazilian-Portuguese. We translated the battery according to Beaton’s guidelines. Psychometric properties were tested, internal consistency was analyzed by Cronbach’s alpha coefficient, test-retest reliability by the intraclass correlation coefficient (ICC). Further, we measured the test execution speed at both times as a temporal stability. Principal component analysis (PCA) was used for structural validity. Evidence of construct validity was assessed through assessment of the relationships with the Wechsler Intelligence Scales. All participants prior to the start of study related activities signed an informed consent form approved by the local ethics committee. A sample of 230 individuals [mean (range) of age: 23 (9 to 60) years; 65% females] was included; a subset of 51 individuals [mean (range) of age: 18 (9 to 57) years, 59% female] completed the Ped-ANAM twice to assess test-retest reliability, and another subset of 54 individuals [mean (range) of age: 20.4 (7 to 62) years; 67% female] completed the Wechsler Intelligence Scales for Children and Adult for assessment of the Ped-ANAM’s construct validity. Our results suggest that the internal consistency of the Ped-ANAM (Cronbach’s α = 0.890) and its subtest test-retest reliability were excellent (ICC: 0.59 to 0.94). There was no clustering in the Principal Components Analysis, suggestive of non-grouping of the evaluated variables. Construct validity assessment to the Wechsler Scales showed expected ranges of low to strong correlations (Spearman correlations: ρ = 0.40 to ρ = 0.69). We concluded that, based on the results of this study, a cross-culturally validated Brazilian-Portuguese version of the Ped-ANAM has been developed and it is a reliable tool for the screening cognitive function.